The Evolving Role of the Press in Contemporary Vietnam - Huong, Le Mai (Richtmann Publishing, 2013)
The aim of this article is to examine the new developments of the mass media in Vietnam in the first decade of the 21st centuryand how they should be responded by the Vietnamese government. Over two decades of rapid economic growth has broughtabout a different face to the Vietnamese economy, presenting a new socio-political environment for the operation of the press.How the Vietnamese Communist Party (VCP) and the Vietnamese Government respond to the emerging role of the press willnot only define the future of the Vietnamese journalism but also reveal the future projection of the VCP.